Forging Smarter Cities through CrowdLaw - Noveck, Beth Simone (2018)
Public officials are often ill-equipped when it comes to knowing how to regulate complex societal challenges, especially those that involve cutting-edge scientific and technological advances that raise myriad ethical, moral, political, legal, regulatory and social questions. But what if technology could be used to improve the quality of regulation and legislation? Online, tech-enabled participation methods, known as “CrowdLaw”, enable more individuals, not only interest groups, to inform the legislative and policymaking processes. In this brief commentary, I survey a handful of global examples which show CrowdLaw in use at each stage of the lawmaking process at the local level and exhibit how participation is improving outcomes.